A Systematic Literature Review of Sustainable Manufacturing: Green Manufacturing Practices in Asia - Sri Susilawati Islami; Mustafa Maulana Pane; Annisa Ghina Salsabila; Beatrice Hillary Sinawang; Ivanna Caroline Tarabu; Lazuardi Fauzan Primaputra (Faculty of Engineering and Technology, Sampoerna University, 2023)
Sustainable manufacturing is a popular topic due to its importance. Green manufacturing practices have been widely applied in Asia. This study aims to provide a comprehensive overview of the current state of knowledge on sustainable manufacturing practices in Asia, with a particular emphasis on green manufacturing practices. Based on the systematic literature review using VOSViewer software to analyze the content of the published articles, the literature on sustainable manufacturing practices can be classified into three main categories, which are Sustainable manufacturing, Sustainability practices, and Environmental management. Most of the literature related to Green & sustainable science & technology, Environmental Science, Engineering, Manufacturing, Engineering, Environmental, and Environmental Studies that is accounted by 18.84%, 17.39%, 10.41%, 10.41% and 8.70% of the total documents included in the review, respectively.